2021
DOI: 10.2147/rmhp.s311830
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Care for COVID-19 Patients Among Nurses Working at Health Care Institutions of Debre Tabor Town, North Central Ethiopia

Abstract: Background Coronavirus disease 2019 (COVID-19) has caused many challenges for health care providers. Nurses meet patients with coronavirus disease and offer care for newly communicable diseases. Despite global and national efforts to prevent the spread, the outbreak is still on a rise, and studies on the health care behaviors of nurses were scarce in the study setting. Therefore, this study was intended in addressing nurses’ intention to care for coronavirus disease 19 patients and its determinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
(46 reference statements)
3
11
0
Order By: Relevance
“…Consistent with earlier research findings in the contexts of Australia (61%) (Lord et al, 2021 ) and Ethiopia (59.5%) (Minuye et al, 2021 ), the majority of the nurses/student nurses (63.4%) in the present study would volunteer to care for COVID‐19 patients. In mainland China, the proportions of nurses willing to join the COVID‐19 frontline were reported as between 92% and 96% during the first wave of COVID‐19 (Ke et al, 2021 ; Luo et al, 2021 ; Wu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with earlier research findings in the contexts of Australia (61%) (Lord et al, 2021 ) and Ethiopia (59.5%) (Minuye et al, 2021 ), the majority of the nurses/student nurses (63.4%) in the present study would volunteer to care for COVID‐19 patients. In mainland China, the proportions of nurses willing to join the COVID‐19 frontline were reported as between 92% and 96% during the first wave of COVID‐19 (Ke et al, 2021 ; Luo et al, 2021 ; Wu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…According to Ajzen ( 2011 ), the TPB is most appropriate for predicting behaviours that are beyond one's volitional control, as is the case of caring for patients with emerging infectious diseases. Indeed, previous studies have used this model to explain up to 55% of variance in nurses' and student nurses' intention to provide care in the contexts of COVID‐19 (Cheng et al, 2021 ; Minuye et al, 2021 ; Tran et al, 2021 ), SARS (Ko et al, 2004 ), H1N1 (Jeong et al, 2015 ) and emerging infectious diseases (Lee & Kang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct comparison of results was not feasible as no study has yet explored the influence of this subjective judgment on nurses’ intention to care in a crisis such as the COVID-19 pandemic. Results for this study can be interpreted in the same ways as the findings from Ko et al [ 35 ], which suggested the need for continuing education to induce intention to care in SRAS patients, have previous emergency and disaster experience [ 36 ], findings from previous studies that report nurses’ increased intention to respond if they have previous experience in caring for patients with infectious diseases [ 37 ], and previous studies that report relationship of confidence in personal skills with willingness to work [ 38 ]. This indicates that providing an opportunity for nurses to gain sufficient knowledge and experience regarding novel infectious diseases can promote their participation in a pandemic or related crisis.…”
Section: Discussionsupporting
confidence: 70%
“…One study showed that work-environment risk category were found to have a significant positive relationship with the nurses' willingness to care for patients with COVID-19, which is a strong predictor for nurses' willingness ( 9 ). Adaptation susceptibility, threat prediction, fear, understanding of coronavirus disease, the occurrence of workplace death, understanding of disease transmission and casualty, negative beliefs, work pressure, social pressure, normative beliefs, and subjective norms have been identified as factors influencing nurses' care of infectious patients ( 11 ). Nurses with a higher level of knowledge were more willing to work with COVID-19 patients ( 10 ).…”
Section: Introductionmentioning
confidence: 99%